2022
DOI: 10.1097/wnr.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted default mode network and executive control network are associated with depression severity on structural network

Abstract: Objective Major depressive disorder (MDD) is a psychiatric disorder with a relatively limited response to treatment. It is necessary to better understand the neuroanatomical mechanisms of structural networks. MethodsThe current study recruited 181 first-onset, untreated adult MDD patients: slight MDD (SD, N = 23), moderate MDD (MD, N = 77), Heavy MDD (HD, N = 81) groups; along with a healthy control group (HC, N = 81) with matched general clinical data. FreeSurfer was used to preprocess T1 images for gray matt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…It is worth noting that researchers have previously found that MDD patients with different severity have different neuroimaging changes in the default mode network (DMN) and the execution control network (ECN) (He et al, 2022 ). Thus, we divided patients with MMD into mild ( N = 24) and moderate ( N = 23) depression groups, and compared the GM volume and FA values of the two groups at baseline and 8 weeks of SG-treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that researchers have previously found that MDD patients with different severity have different neuroimaging changes in the default mode network (DMN) and the execution control network (ECN) (He et al, 2022 ). Thus, we divided patients with MMD into mild ( N = 24) and moderate ( N = 23) depression groups, and compared the GM volume and FA values of the two groups at baseline and 8 weeks of SG-treatment, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Emotional responses originate from the activation of specialised neuronal populations in several parts of the cerebral cortex, notably the ventromedial prefrontal, insula, anterior cingulate, and subcortical structures, such as the amygdala, nucleus accumbens, and ventral striatum [4][5][6][7][8]. The amygdala, located in the medial temporal lobe with an almond-shaped limbic structure, is well known for its role in assigning emotional significance to sensory inputs, affective and emotional states, and related behavioural adaptations [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%